Component Carrier Selection and Beamforming Jointly in LTE-Advanced Heterogeneous Network - Rui Fang; Changyin Sun; Guangyue Lu; Longlong Zheng (Dianxin kexue)
To deal with the interference between macro cell and pico cell, or between pico cell themselves in LTE-Advanced heterogeneous network, joint algorithm of component carrier selection and beamforming was proposed. By shutting down a subset of the component carrier in the dense low power node deployment scenario,it could remove lots of interference at the receive side. Additionally, based on utility function and calculate separately, algorithm reduced the dimensions and the searching complexity of the algorithm. Simulation results show that the proposed scheme can bring a great throughput gain of edge users and the whole system in the heterogeneous network.